Border areas in eastern Bavaria: Once structurally weak, always structurally weak? - Reinhold Koch (Cross-border spatial development in Bavaria: Dynamics in cooperation - Potentials of integration, 2022)
The aim of this paper is to determine whether since 2000 the areas along the border with the Czech Republic have developed in such a way that a location on the border is no longer practically synonymous with structural weakness or whether this is at least less pronounced than it was. Living and working conditions in Bavarian border areas have improved significantly since the turn of the millennium. By 2015 two of the eight districts had reached Bavarian standards. In the two border areas with the lowest rankings the economic situation and conditions on the labour market have also improved, more strongly than the federal average but not to the same extent as the Bavarian average. The analysis was carried out on the basis of a structural indicator, which was used to determine the regions with a particular need for action for the 2013 Bavarian Federal State Development Programme.
urn:nbn:de:0156-41580659; hdl:10419/253270; https://econpapers.repec.org/RePEc:zbw:arlabe:34
Keywords: 710; Federal state development; border areas; structural weakness; regions with a particular need for action; assisted areas; living and working conditions; indicators